Leaves from four different sugarcane varieties as potential renewable feedstocks for second-generation ethanol production: Pretreatments, chemical composition, physical structure, and enzymatic hydrolysis yields. (October 2022) - Espirito Santo, Melissa C.; Kane, Aissata Ousmane; Pellegrini, Vanessa O.A.; Thema, Force Tefo; García, José M.; Acevedo, Alberto; Erazzú, Luis E.; Guimaraes, Francisco E.G.; deAzevedo, Eduardo R.; Polikarpov, Igor
Abstract: Development of Bioeconomy is impossible without establishing efficient technologies of lignocellulosic biomass valorization via transformation into fermentable sugars. Sugarcane is a valuable agricultural crop in several Asian, African, and Latin American countries. Here, leaves from two sugarcane and two energy cane varieties were evaluated for sustainable production of second-generation sugars, and their enzymatic hydrolysis yields were compared. Structural, morphological, and chemical composition changes in sugar and energy cane leaves submitted to acid, and acid-alkaline pretreatments were analyzed using X-ray diffraction, scanning electron microscopy, confocal laser microscopy, high-performance liquid chromatography, and low-field solid-state NMR techniques. Enzymatic hydrolysis assays were conducted to evaluate saccharification yields of untreated and pretreated leaves. Jointly, our results revealed the significant potential of leaves from two commercial sugar cane cultivars currently bred in Argentina as possible lignocellulose substrates for the 2G ethanol industry. Highlights: Potential of leaves from four sugarcane varieties for 2 GE production was investigated. Impacts of pretreatments on the physical structure of the leaves were studied. Side-by-side comparison of enzymatic hydrolysis yields from four cultivars was done. The leaves from two commercial sugarcane cultivars are promising substrates for 2 GE.